Human Capital and Economic Growth in Pakistan - Ali, Hina; Bajwa, Ruqia; Batool, Hadia (Social Science Learning Education Journal, 2016)
This study used human capital and economic growth in Pakistan economy. Income per capital, health and education are the important part for measuring development success in human capital. Housing, education and health play an important role in economic growth. Income per capital alone cannot boost the economic growth and income is not sufficient indicator for human capital and economic growth. Services are very important for economic growth. The role of human capital and technology is very important part for economic growth and power of economic growth. Any country which is unable to develop skills, knowledge, and training to their people is unable to achieve economic growth and development. In this study gross fixed capital (GFC), saving, Inflation, Human capital (HC) Labor force (LF) and foreign direct investment FDI) used as a variables. The data is collected from 1974-2014 time periods. This study is based on time series analysis. In which education is a necessary tool for economic growth. Education enhances the productivity and efficiency of the individuals. In this study ARDL ADF, unit root techniques are used to analyze this study.